Out-Smarting the Host: Bacteria Maneuvering the Immune Response to Favor Their Survival - Mues, Nastaran; Chu, Hong Wei (Frontiers in Immunology, 2020)
Bacteria adapt themselves to various environmental conditions in nature, which can lead to bacterial adaptation and persistence in the host as commensals or pathogens. In healthy individuals, host defense mechanisms prevent the opportunistic bacteria/commensals from becoming a pathological infection. However, certain pathological conditions can impair normal defense barriers leading to bacterial survival and persistence. Under pathological conditions such as chronic lung inflammation, bacteria employ various mechanisms from structural changes to protease secretion to manipulate and evade the host immune response and create a niche permitting commensal bacteria to thrive into infections. Therefore, understanding the mechanisms by which pathogenic bacteria survive in the host tissues and organs may offer new strategies to overcome persistent bacterial infections. In this review, we will discuss and highlight the complex interactions between airway pathogenic bacteria and immune responses in several major chronic inflammatory diseases such as asthma and chronic obstructive pulmonary disease (COPD).